Maroons and blacks torture by Catholic priets, bishop of Lima XVI-XVIII - Cajavilca Navarro, Luis (2015)
The torment and torture that black people suffered causes horror and indignation. The general royal was to undressed the victims, equal men and women ended up totally naked, except with the minimum piece of clothing to cover their ‘shames’. Without worrying about the age or physical conditions of the tortured one. The priests of Cercado de Lima committed inhuman acts against the black of their property. Most of the ‘fugitived’ slaves, were tied in prison, tied to the stairs or to a post to be flogged. The lashes were the most common way of public punishment. They were limited between 50, 100, 200 lashes. In other cases, you could flog someone until kill him or her. The gluteus and back were skinned. The council and popes didn’t say a word about the abolition of the torture. The priests said that those punishments in the ‘light’ of the heretical conceptions were not bad, but a ‘savior remedy’, a balsam for spiritual marks.